Tinea nigra: Relato de caso e revisao da literatura brasileira - Marques, Silvio Alencar [UNESP]; De Camargo, Rosângela Maria Pires (My University, 1996)
The authors present a clinical case of palmar Tinea nigra in a 19-year-old young woman. The Brazilian literature concerning Tinea nigra is discussed as well as the reports presented in Brazilian Congresses from 1985 to 1995. The data show that 63.3% of the cases occurred in patients younger than 20-years-old, they were more frequent among females and 90.5% were localized on the palms; among the cases reported in the Brazilian Congresses those of atypical localization as the back and the genital area are worth noticing.
Tinea nigra: Report of a case and review of the literature
Keywords: epidemiology; Tinea nigra; adult; case report; female; human; tinea